Parity-Driven Disparities in Placenta Previa: A Comprehensive Analysis of Obstetric and Perinatal Factors - Karanfil Yaman, Fikriye; Dogru, Sukran; Ezveci, Huriye; Akkus, Fatih; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: This retrospective cohort study aimed to investigate the incidence of known risk factors for placenta previa in primiparous patients and assess the maternal and fetal outcomes associated with this condition in a tertiary hospital setting. STUDY DESIGN: Data were collected from electronic medical records of pregnant women with confirmed placenta previa who were monitored at our clinic and delivered between January 2016 and June 2024. Demographic characteristics, obstetric history, and perinatal outcomes were analyzed. Statistical analysis was conducted using SPSS version 22, and comparisons between multiparous and nulliparous women were made using appropriate tests. RESULTS: A total of 674 pregnant women were included in the study, comprising 542 multiparous and 132 nulliparous women. Significant differences were observed between the two groups in terms of anesthesia type, transfusion rates, operation duration, and hemoglobin levels. Neonatal outcomes, including APGAR scores, showed variations between multiparous and nulliparous women. However, certain outcomes such as birth weight did not differ significantly between the groups. CONCLUSION: This study provides valuable information on maternal and neonatal outcomes associated with placenta previa in multiparous and nulliparous women. The findings highlight the complex interplay between maternal parity, anesthesia choice, and clinical outcomes and underscore the importance of tailored management approaches in this population.